How do we help women in poor countries break into commercial agriculture? - Puskur, Ranjitha (International Livestock Research Institute, 2011)
Most developing-country women have little control over how the farm income they generate is spent. And when women’s income-generating farm work does become profitable, it is often taken over by men. In this film, Ranjitha Puskur, an innovations researcher at the International Livestock Research Institute (ILRI), describes the challenges of designing and implementing agricultural programs that put money into the pockets of poor rural women.